‘Translating Narrative into Code’ – Thoughts on a Technology-Centric Model of Digital Games as Programmable Media - Werning, Stefan (Eludamos: Journal for Computer Game Culture, 2007)
The current surge of game studies literature demands a scrutinizing look at the solidifying positions within the German and international discourse and the opportunities of finding a common vocabulary and adequate set of analytical tools. In order to arrive at an integrative model of analysis, the intricate interplay of narrative and game mechanics (narratology vs. ludology) is considered from a comparative perspective and thus demystified. Consequently, a new model based on programming theory (object-oriented narrative) is proposed which takes into account elements of psychology, narratological concepts derived from film- and literature studies and cultural studies approaches leading to a ‘close reading’ of games. The article is based on the assumption that computer- and videogames recode the act of ‘reading’ games as texts into a mode of ‘text-processing’ and thereby fundamentally modify the parameters of our cultural appropriation and media literacy.The model proposed herein shall then be tentatively applied to the complex re-staging and re-examination of ‘the real’ in a wide range games from Wonderland to Enter the Matrix.